Low molecular weight of hydroxyethyl cellulose to extract proteins in natural rubber latex - Dung, Lai Thi Kim; Tuan, Le Nghiem Anh; Du, Bui Duy (Vietnam Journal of Science and Technology, 2021)
Natural rubber latex (NRL) with “low protein content” is regarded as less allergenic latex for medical gloves, medical products, condoms, etc. Therefore, this study was conducted to strengthen the fundamental approach of making “low protein NRL” via oligosaccharide hydroxyl ethyl cellulose (oligoHEC) treatment. OligoHEC (Mw ~10,000 g/mol) is degradation product of HEC (Mw ~90,000 g/mol) by 1.5% H2O2 treatment combined with hydrothermal at temperature for 30 minutes at 121°C, pressurized rate of 0.38 mPa by autoclave equipment. OligoHECs were employed to form electrical bonds with the proteins. The target of this study is protein content of NRL ≤ 50 µg/g of rubber, we surveyed the effect of oligoHEC treatment towards the solution proteins content of NRL. Results show that oligoHEC at low concentration (0.25%) effectively extracted the proteins molecules. Interestingly, allergenic proteins content of NRL serum was decreased proportionally (< 50 µg/g of rubber) with the upsurge of oligoHEC concentration, suggesting deactivation of allergenic. These preliminary results indicate a potential approach to produce low allergenic risk NRL products with adding of oligoHEC